1982
DOI: 10.1073/pnas.79.4.1106
|View full text |Cite
|
Sign up to set email alerts
|

Effect of methylation on expression of microinjected genes.

Abstract: The cloned genes for the simian virus 40 large tumor antigen and for herpes simplex virus (HSV) thymidine kinase (TK) were methylated with EcoRI methylase. The genes were microinjected into the nuclei of TK-deficient (tk-) cells, and expression of the genes was determined by immunofluorescence staining for the simian virus 40 large tumor antigen and by [3H]thymidine incorporation followed by autoradiography for HSV TK. We found that methylation of the simian virus 40 gene, under EcoRI Recently, a number of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
0
1

Year Published

1983
1983
1999
1999

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(30 citation statements)
references
References 37 publications
4
25
0
1
Order By: Relevance
“…Analysis of the methylation pattern of the viral thymidine kinase (TK) gene in Herpes simplex virus (HSV)-transformed mouse cells showed that when the gene was being actively transcribed it was unmethylated, when inactive it was methylated, and when induced to activity by 5-AzaCyt it was again unmethylated. This finding was extended by Waechter & Baserga (1982) who found that when the cloned gene for HSV-TK was methylated with Eco RI methylase and microinjected into the nucleus of TK"-) cells, methylation at particular sites markedly reduced or abolished the expression of the gene. These authors pointed out the possibility that different genes might respond differently to methylation, since similar Eco RI methylation of the gene coding for Simian virus 40 T antigen had no effect upon its expression after microinjection.…”
Section: -Mc Depletion During Tumour Developmentmentioning
confidence: 87%
“…Analysis of the methylation pattern of the viral thymidine kinase (TK) gene in Herpes simplex virus (HSV)-transformed mouse cells showed that when the gene was being actively transcribed it was unmethylated, when inactive it was methylated, and when induced to activity by 5-AzaCyt it was again unmethylated. This finding was extended by Waechter & Baserga (1982) who found that when the cloned gene for HSV-TK was methylated with Eco RI methylase and microinjected into the nucleus of TK"-) cells, methylation at particular sites markedly reduced or abolished the expression of the gene. These authors pointed out the possibility that different genes might respond differently to methylation, since similar Eco RI methylation of the gene coding for Simian virus 40 T antigen had no effect upon its expression after microinjection.…”
Section: -Mc Depletion During Tumour Developmentmentioning
confidence: 87%
“…Studies with inhibitors of DNA methylation suggest that the inhibition of DNA methylation increases the frequency of expression of methylated, inactive genes in vivo (2,4,9,20), and it has been demonstrated that methylated DNA is expressed more poorly than unmethylated DNA after transfer into mammalian cells (18,25,33, 36).…”
mentioning
confidence: 99%
“…When methyladenine was placed at the EcoRI sites with EcoRI methylase and the gene was then microinjected into L cells, TK expression was reduced (35). The authors (35) pointed out that one of the EcoRI sites, the same one we observed to be methylated de novo, was the CCAAT box for the TK gene. This sequence is thought to be an element of the promoter (2,7).…”
Section: Resultsmentioning
confidence: 99%
“…When the gene was methylated at CCGG by HpaII methylase and then was transferred into L cells, the frequency of TK+ transformants was reduced, but not to zero (25,39). When methyladenine was placed at the EcoRI sites with EcoRI methylase and the gene was then microinjected into L cells, TK expression was reduced (35). The authors (35) pointed out that one of the EcoRI sites, the same one we observed to be methylated de novo, was the CCAAT box for the TK gene.…”
Section: Resultsmentioning
confidence: 99%